Regulating Vessel Biofouling to Support New Zealand’s Marine Biosecurity System – A Blue Print for Evidence-Based Decision Making - Georgiades, Eugene; Kluza, Daniel; Bates, Tracey; Lubarsky, Katie; Brunton, Jennie; Growcott, Abraham; Smith, Trecia; McDonald, Simon; Gould, Brendan; Parker, Naomi; Bell, Andrew (Frontiers in Marine Science, 2020)
A healthy marine environment is integral to many of New Zealand’s economic, social and cultural values, which include fisheries, aquaculture, tourism, and recreational and customary activities. The introduction and spread of marine non-indigenous species (NIS) via the vessel biofouling pathway may put these values at risk. Over the past two decades, the Ministry for Primary Industries (MPI) has been proactive in commissioning research focused on the risks associated with vessel biofouling, identification of potential risk vessels, and risk management options. In 2010, MPI consulted on options to manage the biofouling risks on all vessels entering New Zealand waters. In 2014, New Zealand became the first country to introduce mandatory biofouling requirements. Between 2014 and 2018, MPI focused on communicating the requirements to support stakeholder awareness, readiness and uptake. In parallel, MPI commissioned further research to investigate proactive and reactive approaches to biofouling management. Research outcomes were summarized and technical advice provided to inform stakeholders of what constitutes best biofouling management practices. This review summarizes MPI’s research and technical advice on the risks associated with vessel biofouling and its management, and the procedures followed to produce New Zealand’s biofouling regulations. The development of these regulations is also contextualized in terms of New Zealand’s marine biosecurity system. The transparent and evidence-based approach followed by MPI provides a blueprint for establishing biofouling regulations. Because these regulations are based on International Maritime Organization guidelines, there is the potential to develop consistent global and domestic practices for managing marine NIS introduction and spread.